End‐of‐life care following leg amputation in patients with peripheral artery disease or diabetes. Issue 1 (14th October 2019) - de Mestral, C.; Hsu, A. T.; Talarico, R.; Lee, D. S.; Hussain, M. A.; Salata, K.; Al‐Omran, M.; Tanuseputro, P.
Abstract : Background: The aim was to characterize end‐of‐life care in patients who have had a leg amputated for peripheral artery disease (PAD) or diabetes. Methods: This was a population‐based retrospective cohort study of patients with PAD or diabetes who died in Ontario, Canada, between 2011 and 2017. Those who had a leg amputation within 3 years of death were compared with a control cohort of deceased patients with PAD or diabetes, but without leg amputation. The patients were identified from linked health records within the single‐payer healthcare system. Place and cause of death, as well as health services and costs within 90 days of death, were compared between the amputee and control cohorts. Among amputees, multivariable regression models were used to characterize the association between receipt of home palliative care and in‐hospital death, as well as time spent in hospital at the end of life. Results: Compared with 213 300 controls, 3113 amputees were less likely to die at home (15·5 versus 24·9 per cent; P  < 0·001) and spent a greater number of their last 90 days of life in hospital (median 19 versus 8 days; P  < 0·001). Amputees also had higher end‐of‐life healthcare costs across all sectors. However, receipt of palliative care was less frequent among amputees than controls (inpatient: 13·4 versus 16·8 per cent, P  < 0·001; home: 14·5 versus 23·8 per cent, P  < 0·001). Among amputees, receipt of home palliative care was associated with a lower likelihood of in‐hospital death (odds ratio 0·49, 95 per cent c.i. 0·40 to 0·60) and fewer days in hospital (rate ratio 0·84, 0·76 to 0·93). Conclusion: Palliative care is underused after amputation in patients with PAD or diabetes, and could contribute to reducing in‐hospital death and time spent in hospital at the end of life. Abstract : This was a population‐based study of end‐of‐life care and health costs in amputees with peripheral artery disease or diabetes. Palliative care was underused after major amputation, and may contribute to reducing in‐hospital death and time spent in hospital at the end of life. Plea for more palliative care Abstract : Antecedentes: Caracterizar la atención al final de la vida en pacientes con amputación de la extremidad inferior por enfermedad arterial periférica ( peripheral arterial disease, PAD) o diabetes. Métodos: Se trata de un estudio de cohortes retrospectivo de base poblacional en sujetos fallecidos con PAD o diabetes en Ontario, Canadá (2011‐2017). A partir de los registros sanitarios incluidos en un sistema de salud de una sola entidad pagadora, se identificaron los individuos con amputación de la extremidad inferior en los 3 años previos al fallecimiento y una cohorte control de fallecidos con PAD o diabetes sin amputación. Entre las cohortes de amputados y controles se comparó el lugar del fallecimiento y la causa, así como el uso de servicios sanitarios y costes en los últimos 90 días de vida. En el grupo de los amputados, se utilizaron modelos de regresión para caracterizar la asociación entre recibir cuidados paliativos domiciliarios y el fallecimiento en el hospital, así como los días de estancia hospitalaria al final de la vida. Resultados: En comparación con los controles ( n = 213.300), los sujetos con amputación ( n = 3.113) era menos probable que fallecieran en el domicilio (16% versus 25%, P < 0, 001) y pasaron un mayor número de sus últimos 90 días de vida en el hospital (mediana 19 versus 8 días, P < 0, 001). Los costes de atención sanitaria al final de la vida en todos los sectores también fueron mayores para los amputados. Sin embargo, recibir cuidados paliativos fue menos frecuente en los amputados que en los controles (en el hospital 13% versus 17%, P < 0, 001; domiciliarios 14% versus 24%, P < 0, 001). En el grupo de los amputados, recibir cuidados paliativos domiciliarios se asociaba con una menor probabilidad de fallecimiento en el hospital (razón de oportunidades, odds ratio 0, 49, i.c. del 95% 0, 40‐0, 60) y menos días de hospitalización (tasa de riesgo 0, 84, i.c. del 95% 0, 76‐0, 93). Conclusión: Los cuidados paliativos están infrautilizados en pacientes con PAD o diabetes y pueden contribuir a disminuir los fallecimientos en el hospital y los días de hospitalización al final de la vida.